The Innovation Learning Thematic Through E-learning Madrasah for Moment Covid-19 pandemic at Madrasah Ibtida'iyah Ma'arif 01 KH. Siddiq Jember. thesis. Study Program Madrasah Ibtidaiyah Teacher Education Postgraduate UIN KHAS Jember. - SHOFIYAH, SITI (IJIT: Indonesian Journal of Islamic Teaching, 2021)
This article discusses the Thematic Learning Innovation Through Madrasa E-learning During the Covid-19 Pandemic at Madrasa Ibtida'iyah Ma'arif 01 KH. Siddiq Jember. This study uses a qualitative approach by conducting observations, interviews and documentation. Data analysis uses Miles and Huberman interactive data analysis. The validity of the data is source triangulation, technique triangulation and member check. The findings of this study are learning material innovation, learning method innovation, and learning media innovation. Online learning activities through e-learning madrasas are innovated by each class teacher in thematic learning.